Es gibt Alternativen zur ALCA: ALBA und warum der ALCA-Prozess gestoppt wurde - Garcia, Ana (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
The Free Trade Agreement of the Americas (FTAA) could not be set up in the way and time the US-Government firstly wanted. Among others, one of the main reasons was the wide spread network resistance that involved trade unions, social movements and grass roots organizations from North and South America, who worked together to pressure their governments to stop negotiations. A new space for action has emerged in the last few years with the election of left-wing Presidents in South America, converging interest of governments with demands from social movements to overcome neoliberal regional integration. A concrete alternative project against FTAA came up from the cooperation agreement between Venezuela und Cuba, but extended to other countries: The "bolivarian" Alternative for the Americas and Caribbean (ALBA) seeks to establish solidary ways of integration in Latin America.